Optimal inductor design for nanofluid heating characterisation. Issue 7 (5th October 2015) - Bertani, Roberta; Ceretta, Flavio; Di Barba, Paolo; Dughiero, Fabrizio; Forzan, Michele; Michelin, Rino Antonio; Sgarbossa, Paolo; Sieni, Elisabetta; Spizzo, Federico
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Magnetic fluid hyperthermia experiment requires a uniform magnetic field in order to control the heating rate of a magnetic nanoparticle fluid for laboratory tests. The automated optimal design of a real-life device able to generate a uniform magnetic field suitable to heat cells in a Petri dish is presented. The paper aims to discuss these issues. Design/methodology/approach – The inductor for tests has been designed using finite element analysis and evolutionary computing coupled to design of experiments technique in order to take into account sensitivity of solutions. Findings – The geometry of the inductor has been designed and a laboratory prototype has been built. Results of preliminary tests, using a previously synthesized and characterized magneto fluid, are presented. Originality/value – Design of experiment approach combined with evolutionary computing has been used to compute the solution sensitivity and approximate a 3D Pareto front. The designed inductor has been tested in an experimental set-up.